1997
DOI: 10.1002/(sici)1096-8628(19971031)72:3<257::aid-ajmg2>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Xq28‐linked noncompaction of the left ventricular myocardium: Prenatal diagnosis and pathologic analysis of affected individuals

Abstract: Isolated noncompaction of the left ventricular myocardium (INVM) is characterized by the presence of numerous prominent trabeculations and deep intertrabecular recesses within the left ventricle, sometimes also affecting the right ventricle and interventricular septum. Familial occurrence of this disorder was described previously. We present a family in which 6 affected individuals demonstrated X-linked recessive inheritance of this trait. Affected relatives presented postnatally with left ventricular failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
1
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 0 publications
2
96
1
10
Order By: Relevance
“…The clinical and pathological features are similar to those reported by Chin et al and Bleyl et al Chin et al (1990) first reported four patients of familial occurrence. Later, two patients were presented by Shinozaki et al (1995), four from one family by Hamamichi et al (1996), two from one family by Ritter et al (1997), and six from one family by Bleyl et al (1997a). Within these seven families, including our case, all but one finding occurred in sibs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and pathological features are similar to those reported by Chin et al and Bleyl et al Chin et al (1990) first reported four patients of familial occurrence. Later, two patients were presented by Shinozaki et al (1995), four from one family by Hamamichi et al (1996), two from one family by Ritter et al (1997), and six from one family by Bleyl et al (1997a). Within these seven families, including our case, all but one finding occurred in sibs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…4 Clinical manifestations of the disorder included depressed LV systolic function, ventricular arrhythmias, and systemic embolization. [3][4][5] Both sporadic and familial 4,6,7 forms have been described.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, however, the echocardiogram of the younger brother appeared to be normal at 20 weeks of gestation. It is not clear whether these findings were related to limitations of the fetal echocardiography technique or to the postnatal development of the disorder (14). Left ventricular noncompaction has mostly been associated with disorders causing skeletal muscle or cardiac disease, or with chromosomal anomalies (15,16).…”
Section: Discussionmentioning
confidence: 89%